1972
DOI: 10.1149/1.2404020
|View full text |Cite
|
Sign up to set email alerts
|

Phase Equilibria in Lithium-Chalcogen Systems

Abstract: The equilibrium phase diagram of the lithium‐sulfur system has been investigated. A miscibility gap extends from 0.2 to 37.0 atom per cent (a/o) lithium above a monotectic temperature of 364.8°C; the critical temperature is greater than 600°C. The only intermediate phase found is Li2S , which melts at 1372°C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
0

Year Published

1973
1973
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 6 publications
5
36
0
Order By: Relevance
“…While GeS 2 glass powder is verified to be amorphous, Li 2 S powder shows several sharp peaks. The XRD pattern of the Li 2 S powder closely matches the JCPDS data (Cunningham et al, 1972). From the JCPDS data, it is verified that the system and space group of Li 2 S powder are face-centered cubic and Fm-3m, respectively (Cunningham et al, 1972 Li 4 GeS 4 reference (Komiya et.…”
Section: X-ray Diffraction Of the Starting Materials And Targetssupporting
confidence: 67%
“…While GeS 2 glass powder is verified to be amorphous, Li 2 S powder shows several sharp peaks. The XRD pattern of the Li 2 S powder closely matches the JCPDS data (Cunningham et al, 1972). From the JCPDS data, it is verified that the system and space group of Li 2 S powder are face-centered cubic and Fm-3m, respectively (Cunningham et al, 1972 Li 4 GeS 4 reference (Komiya et.…”
Section: X-ray Diffraction Of the Starting Materials And Targetssupporting
confidence: 67%
“…Although we also attempted to synthesize Li 2 S 4 powder, it could not be isolated, because it is thermodynamically unstable. 27,40 Since the XANES features of Na 2 S 4 (27,28) are similar to the predicted features of lithium polysulfides, 29 it is a suitable reference for a qualitative analysis.…”
Section: Methodsmentioning
confidence: 87%
“…It was reported that Li could react with sulfur to form Li 2 S n (n=1,2,...) [11]. The discharge behavior might be related with the formation of Li 2 S, which is a stable phase between Li and S [19].…”
Section: Resultsmentioning
confidence: 99%